Exploration of Mathematics Concepts in QS An-Nur - Nadya Febriani Meldi; Sugiatno Sugiatno; Asep Nursangaji; Dede Suratman; Zubaidah Zubaidah; Hamdani Hamdani (JETL (Journal of Education, Teaching and Learning), 2022)
This article reveals exploration of mathematical models and concepts in QS An-Nur: 24:26. This research stems from the ineffectiveness of learning mathematics because the process does not begin with students' initial understanding. In fact, according to NCTM, teaching and learning will be effective if it starts from what students know. In Islamic school students, initial knowledge can be extracted from the Qur'an because the Qur'an is a learning tool in believing in Islam, so it is recognized that the verses of the Qur'an are contained in the cognitive structure of students, which can facilitate learning. Unfortunately, the sources of learning mathematics and the Qur'an used by Islamic schools have not covered all topics of learning mathematics, so to complete it, it is necessary to model the verses of the Qur'an related to mathematics. This research was conducted to obtain mathematical modeling and concepts at the high school/equivalent level using the Miles and Huberman analysis method combined with Blum and Leib modeling and Abdussakir theory and Pseudo concrete. Based on the combination of analytical theory, the modeling and mathematical concepts contained are relations, surjective and bijective functions, inverse functions, and reflections.